Validation of Plasmodium falciparum deoxyhypusine synthase as an antimalarial target - Aroonsri, Aiyada (PeerJ, 2019)
BACKGROUND: Hypusination is an essential post-translational modification in eukaryotes. The two enzymes required for this modification, namely deoxyhypusine synthase (DHS) and deoxyhypusine hydrolase are also conserved. Plasmodium falciparum human malaria parasites possess genes for both hypusination enzymes, which are hypothesized to be targets of antimalarial drugs. METHODS: Transgenic P. falciparum parasites with modification of the PF3D7_1412600 gene encoding PfDHS enzyme were created by insertion of the glmS riboswitch or the M9 inactive variant. The PfDHS protein was studied in transgenic parasites by confocal microscopy and Western immunoblotting. The biochemical function of PfDHS enzyme in parasites was assessed by hypusination and nascent protein synthesis assays. Gene essentiality was assessed by competitive growth assays and chemogenomic profiling. RESULTS: Clonal transgenic parasites with integration of glmS riboswitch downstream of the PfDHS gene were established. PfDHS protein was present in the cytoplasm of transgenic parasites in asexual stages. The PfDHS protein could be attenuated fivefold in transgenic parasites with an active riboswitch, whereas PfDHS protein expression was unaffected in control transgenic parasites with insertion of the riboswitch-inactive sequence. Attenuation of PfDHS expression for 72 h led to a significant reduction of hypusinated protein; however, global protein synthesis was unaffected. Parasites with attenuated PfDHS expression showed a significant growth defect, although their decline was not as rapid as parasites with attenuated dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) expression. PfDHS-attenuated parasites showed increased sensitivity to N(1)-guanyl-1,7-diaminoheptane, a structural analog of spermidine, and a known inhibitor of DHS enzymes. DISCUSSION: Loss of PfDHS function leads to reduced hypusination, which may be important for synthesis of some essential proteins. The growth defect in parasites with attenuated Pf DHS expression suggests that this gene is essential. However, the slower decline of PfDHS mutants compared with PfDHFR-TS mutants in competitive growth assays suggests that PfDHS is less vulnerable as an antimalarial target. Nevertheless, the data validate PfDHS as an antimalarial target which can be inhibited by spermidine-like compounds.